CONSUMERS WILLINGNESS TO PAY FOR PORANG RICE IN MEDAN CITY - Syaifullah, Adli Nadhif; Sihombing, Vista Uli; Ginting, Kristiawan Hadinata; Siregar, Futri Medwina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
A healthy lifestyle and the desire to avoid various diseases motivate consumers to switch to healthy foods such as porang rice. However, the limited availability of porang rice products in various cities such as Medan makes the price expensive, so most consumers still do not regularly buy porang rice, while some consumers buy it regularly. This study aims to analyze consumers' willingness to pay for porang rice in Medan City and the various factors influencing it. The study uses primary data with a snowball sampling method and sample calculation using the Lemeshow formula, resulting in 100 porang rice consumers as the sample. The data was analyzed using the contingent valuation method and logistic regression. The results of the study indicate that consumers' willingness to pay for porang rice has increased compared to the previous price, ranging from 0.79% to 8.68%. The study also revealed that variables such as occupation, ease of access, and health significantly influence consumers' willingness to pay for porang rice, while other factors such as age, education level, income, number of family members, and gender do not significantly influence consumers' willingness to purchase porang rice.